Pengaruh CR dan DER Terhadap ROA Pada Perusahaan Makanan & Minuman - Fira Ocdalina Fianti; Ine Mayasari; Endang Hatma Juniwati (Indonesian Journal of Economics and Management, 2022)
This research to see effect of liquidity and solvency ratios on profitability in 6 samples of food baverage companies listed on IDX in 2014-2018. The independent variables use are CR, DER. Dependent variables is ROA. The method use in this research is quantitative method. Data collection technique is a method of documentation. Data analysis used is multiple regression analysis using IBM SPSS Statistics 26 software. The Result that the CR parisial has a significant effect on ROA while the DER has no significant effect on ROA. Simultaneously, CR and DER have a positive and significant effect of ROA. Based on the result of the calculation of the coefficient of determination test, it’s know that the R square value is 0,567. Which means that simultaneously the CR and DER variables have an effect on ROA by 56,7%. While the remaining 43,3% is influenced by other variables not axamined in this study.